2003
DOI: 10.1103/physreve.68.021921
|View full text |Cite
|
Sign up to set email alerts
|

Structure, dynamics, and energetics of water at the surface of a small globular protein: A molecular dynamics simulation

Abstract: The dynamics of water around a biomolecular surface has attracted a lot of attention recently. We report here protein-solvent simulation studies of the small globular protein ubiquitin (human). The simulations are run unconstrained, without freezing the bonds. The mean square displacements of the water oxygen atoms show a sublinear trend with time. The diffusion coefficient data indicate that the water in the first hydration layer behaves like water at a temperature that is roughly 12 degrees C lower than the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 44 publications
6
64
1
Order By: Relevance
“…The diffusion rate perpendicular to the peptide surface is slower than the overall diffusion while the parallel diffusion is found to be faster. As observed in other simulations 14,32 and experimental results, 33 the anisotropy in the parallel and perpendicular water mobility seems to be connected to the dipole and H-bonding of structured water, especially in the first hydration layer of the protein surface. 10,34 Interactions of protein residues with neighboring water molecules can orient water dipoles normal to the protein surface.…”
Section: A Solvent Diffusion Near Peptide Surfacesupporting
confidence: 60%
See 1 more Smart Citation
“…The diffusion rate perpendicular to the peptide surface is slower than the overall diffusion while the parallel diffusion is found to be faster. As observed in other simulations 14,32 and experimental results, 33 the anisotropy in the parallel and perpendicular water mobility seems to be connected to the dipole and H-bonding of structured water, especially in the first hydration layer of the protein surface. 10,34 Interactions of protein residues with neighboring water molecules can orient water dipoles normal to the protein surface.…”
Section: A Solvent Diffusion Near Peptide Surfacesupporting
confidence: 60%
“…7,10,14,16,32,33 The self-diffusion coefficient of solvent is expected to decrease when approaching the protein surface. We evaluate the diffusion coefficient of water, along with its parallel and perpendicular components, as a function of distance to the peptide surface ͑Fig.…”
Section: A Solvent Diffusion Near Peptide Surfacementioning
confidence: 99%
“…They showed the existence of a hydration shell whose average density is around 10% larger than that of the bulk water. Molecular dynamics simulation studies also suggested that the variation in the first hydration shell density is subject to the electrostatic properties of the protein surface and local surface topography (Makarov et al, 1998(Makarov et al, , 2000Dastidar & Mukhopadhyay, 2003). However, the properties of the hydrated water shells are still the subject of many experimental and theoretical investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Further, at a particular temperature, the value of D is minimum for the water molecules around the minor groove of the DNA and maximum for bulk water. The value of the diffusion coefficient, D for the bulk water corresponding to a temperature of 300 K is 2.62 × 10 −5 cm 2 /s, closely matched with the value obtained from simulation of pure water [92]. Additionally, if we assume homogeneous, isotropic, three dimensional liquids, then < r 2 > ∼ t. Due to the presence of anomalous diffusion, the MSD follows the law,…”
Section: Diffusion Properties Of the Water Moleculesmentioning
confidence: 54%